Composition of Seagrass Root Associated Bacterial Communities Are Linked to Nutrients and Heavy Metal Concentrations in an Anthropogenically Influenced Estuary - Martin, Belinda C.; Middleton, Jen A.; Skrzypek, Grzegorz; Kendrick, Gary A.; Cosgrove, Jeff; Fraser, Matthew W. (Frontiers in Marine Science, 2022)
Seagrasses are globally recognized as bioindicators of marine eutrophication and contamination. Seagrasses also harbor a distinct root microbial community that largely reflects the conditions of the surrounding environment as well as the condition of the seagrass. Hence monitoring changes in the root microbial community could act as an additional biological indicator that reflects both the seagrass health condition, as well as potential deterioration in coastal waters. We used 16S rRNA gene sequencing combined with analysis of seagrass nutrients (C, N, δ15N, δ13C) and tissue metal concentrations to investigate potential links between seagrass (Halophila ovalis) root bacteria and seagrass nutrient and metal concentrations within an anthropogenically influenced estuary. We found seagrass tissue nitrogen (%) and δ15N values were 2–5 times higher than global averages for this species. Seagrass root associated bacteria formed distinct communities that clustered by site and were correlated to both seagrass nutrient and metal concentration, with some putative sulfide oxidizing bacteria (Sulfurimonas and Sulfurovum) correlated with greater nutrient concentrations, and putative iron cycling bacteria (Lewinella and Woeseia) correlated with greater Fe and As concentrations. Our findings shed further light on the relationship between seagrass and their microbes, as well as provide additional assessment of the use of both seagrass and their microbes as indicators of estuarine and seagrass condition.